(untitled) (Revista Argentina de Cirugía, 2021)
Background: the diagnosis of acute appendicitis is based on physical examination and expe-rience. 7.6% of the population will be operated on for appendicitis. Negative appendectomy reaches 20%. Alvarado proposed 8 criteria to reduce the number of negative appendectomy. Objective: assess the implementation of Alvarado’s criteria in diagnosis of acute appendicitis. Method: of the total 801 appendectomies operated between January 2006 and March 2013, two groups were generated. Group 1 was used as control, and included patients operated between 2006- 2011 and were operated accordingly to the surgeon criteria. In Group 2, appendectomy was decided using the Alvarado criteria. Results: men represented 50.6%. Average age 40 years. Hospital stay 2.64 days. Group 1, in-cluded 598 total appendectomies and 124 negative appendectomies (20.7%). Group 2, included 203 patients and 16 (7.8%) A. Ne. POP complications, Group 1: 9.1%, Group 2: 12.8%. Reentry 5,3% and 6,9%, reoperation 3% and 2,9% respectively. Conclusions: Alvarado’s criteria significantly reduce negative appendectomy.